Early Oxidative Stress Response in Patients with Severe Aortic Stenosis Undergoing Transcatheter and Surgical Aortic Valve Replacement: A Transatlantic Study - Michael Mahmoudi; Juan Guillermo Gormaz; Marcia Erazo; Michael Howard; Cristian Baeza; Martin Feelisch; Nick Curzen; Bartosz Olechowski; Bernadette Fernandez; Magdalena Minnion; Monika Mikus-Lelinska; Mia Meiss; et al. (My University, 2019)
Myocardial ischemia/reperfusion-related oxidative stress as a result of cardiopulmonary bypass is thought to contribute to the adverse clinical outcomes following surgical aortic valve replacement (SAVR). Although the acute response following this procedure has been well characterized, much less is known about the nature and extent of oxidative stress induced by the transcatheter aortic valve replacement (TAVR) procedure. We therefore sought to examine and directly compare the oxidative stress response in patients undergoing TAVR and SAVR. A total of 60 patients were prospectively enrolled in this exploratory study, 38 patients undergoing TAVR and 22 patients SAVR. Reduced and oxidized glutathione (GSH, GSSG) in red blood cells as well as the ferric-reducing ability of plasma (FRAP) and plasma concentrations of 8-isoprostanes were measured at baseline (S1), during early reperfusion (S2), and 6-8 hours (S3) following aortic valve replacement (AVR). TAVR and SAVR were successful in all patients. Patients undergoing TAVR were older (79.3±9.5 vs. 74.2±4.1 years; P<0.01) and had a higher mean STS risk score (6.6±4.8 vs. 3.2±3.0; P<0.001) than patients undergoing SAVR. At baseline, FRAP and 8-isoprostane plasma concentrations were similar between the two groups, but erythrocytic GSH concentrations were significantly lower in the TAVR group. After AVR, FRAP was markedly higher in the TAVR group, whereas 8-isoprostane concentrations were significantly elevated in the SAVR group. In conclusion, TAVR appears not to cause acute oxidative stress and may even improve the antioxidant capacity in the extracellular compartment.
Keywords: averages; blood; capacity; cells; plasma; replacement; scores; stresses; aged; aortic valve stenosis; chile; female; follow-up studies; humans; male; oxidative stress; prospective studies; risk factors; stress, physiological; transcatheter aortic valve replacement; treatment outcome; united kingdom; blood; oxidative stress; surgery; 8 isoprostane; glutathione; glutathione disulfide; antioxidant capacity; cardiopulmonary bypass; extracellular compartments; ferric reducing ability of plasmas; oxidative stress response; plasma concentration; reduced and oxidized glutathione; transcatheter aortic valves; aged; aortic stenosis; aortic valve replacement; article; blood analysis; blood level; cardiopulmonary bypass; clinical evaluation; controlled study; disease severity; erythrocyte; female; ferric reducing antioxidant power assay; human; intermethod comparison; major clinical study; male; observational study; oxidative stress; prospective study; society of thoracic surgeons score; transcatheter aortic valve implantation; aortic valve stenosis; chile; follow up; physiological stress; procedures; risk factor; transcatheter aortic valve implantation; treatment outcome; united kingdom; blood vessels